2020
DOI: 10.1186/s12891-020-3160-5
|View full text |Cite
|
Sign up to set email alerts
|

Applying the International Classification of Functioning, Disability and Health framework to determine the predictors of falls and fractures in people with osteoarthritis or at high risk of developing osteoarthritis: data from the Osteoarthritis Initiative

Abstract: Background: Falls are a major cause of injury and death among older people. Evidence suggests that people with osteoarthritis (OA) are at a higher risk of falls and fall-related injuries including fractures. While studies demonstrate a link between OA and falls, little is known about the pathways that link falls with demographic factors, OA impairments, activity limitations and participation restrictions. The aim of this study was to identify risk factors for falls and fractures among people with OA or at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 31 publications
2
22
1
Order By: Relevance
“…However, despite studies demonstrating a link between OA and falls (Dore et al., 2015; Smith, Higson, Pearson, & Mansfield, 2018), there is limited understanding of the prevalence of falls in people with OA especially those aged between 45 and 64 years. It also remains unclear whether the risk factors for falls in this population are similar to those identified in older adults (Soh, Barker, Morello, & Ackerman, 2020). Improving our understanding of modifiable risk factors may guide the design and implementation of tailored falls prevention interventions for this patient group.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, despite studies demonstrating a link between OA and falls (Dore et al., 2015; Smith, Higson, Pearson, & Mansfield, 2018), there is limited understanding of the prevalence of falls in people with OA especially those aged between 45 and 64 years. It also remains unclear whether the risk factors for falls in this population are similar to those identified in older adults (Soh, Barker, Morello, & Ackerman, 2020). Improving our understanding of modifiable risk factors may guide the design and implementation of tailored falls prevention interventions for this patient group.…”
Section: Introductionmentioning
confidence: 85%
“…This differs to previous literature where adults over 50 years of age who were more active were less likely to fall (Peeters et al., 2019; Pereira, Baptista, & Infante, 2014; White et al., 2018). Given that no association was also observed between physical activity and falls in people with OA or those at high risk of developing OA (Soh et al., 2020), further work is needed to determine whether there may be a nonlinear association between mobility and falls in this group of individuals (Barker, Nitz, Low Choy, & Haines, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Falls are a major cause of injury, hospitalization, and death among older people worldwide [ 1 ], and they account for the largest percentage of deaths from unintentional injuries [ 2 ]. Previous systematic reviews demonstrated that a link exists between knee osteoarthritis (OA) [ 3 ] or rheumatoid arthritis (RA) [ 4 ] and falls.…”
Section: Introductionmentioning
confidence: 99%
“…In adults with arthritis, the prevalence of one fall and ≥2 falls within 12 months was 15.5% and 21.3%, respectively, which was higher than that in the controls [ 9 ]. The OA patients’ fall prevalence was high in a few previous studies [ 1 , 10 , 11 ], but these studies evaluated fall prevalence without differentiating between sex and age groups. A review article showed that gender discrepancies exist in fall risk among older individuals with OA [ 12 ].…”
Section: Introductionmentioning
confidence: 99%